Relevansi Metode Berpikir Ilmiah di Era Artificial Intelligence: Analisis Kritis terhadap Transformasi Proses Penelitian Akademik - Indi Nuroini (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines whether the scientific method remains relevant in the era of artificial intelligence (AI), as academic communities increasingly rely on AI to support cognitive and analytical tasks. Using a qualitative phenomenological approach, the research explores the experiences and perceptions of lecturers and students regarding the role of scientific thinking in AI-assisted learning and research. Data were collected through semi-structured interviews, classroom observations, and document analysis involving purposively selected participants who actively use AI in academic activities. The findings reveal three major themes: the shift in cognitive habits toward AI dependence, the tension between technological efficiency and analytical rigor, and the continued relevance of the scientific method in AI-mediated environments. Although AI improves productivity and facilitates academic work, excessive reliance on AI reduces engagement in essential scientific processes, including problem formulation, critical evaluation, and methodological justification. Participants also expressed concerns that AI dependence may weaken reflective judgment and independent verification of information. Nevertheless, the scientific method remains indispensable for ensuring academic integrity, epistemic credibility, and intellectual autonomy. The study concludes that strengthening scientific literacy, critical thinking, and AI literacy through institutional policies and pedagogical strategies is essential to ensure that AI functions as a supportive tool rather than a substitute for human scientific inquiry.